Modern perspectives of study on economic psychology - Mshvidobadze, T. I.; Lomsadze, K. C.; Toliashvili, B. K. (Dnipro University of Technology, 2025)
This scientific work uses a comprehensive approach that combines descriptive, analytical and explanatory research methods. The use of these methods allowed us to deeply highlight the key issues under consideration and provide a systematic overview of the subject. The descriptive method was used to systematize and present existing scientific views on economic psychology, which became the basis for further analysis. The analytical method allowed us to study in detail various approaches and theories, identify their strengths and weaknesses, and establish relationships between economic and psychological factors of human behavior. The explanatory method contributed to the substantiation of the conclusions drawn, the disclosure of the essence of economic and psychological phenomena and the formulation of conceptual provisions. Дана наукова праця використовує комплексний підхід, що поєднує описові, аналітичні та пояснювальні методи дослідження. Застосування цих методів дозволило глибоко висвітлити ключові проблеми, що розглядаються, та надати системний огляд предмета. Описовий метод використано для систематизації та представлення існуючих наукових поглядів на економічну психологію, що стало основою для подальшого аналізу. Аналітичний метод дозволив детально вивчити різні підходи та теорії, виявити їхні сильні та слабкі сторони, а також встановити взаємозв’язки між економічними та психологічними чинниками поведінки людини. Пояснювальний метод сприяв обґрунтуванню зроблених висновків, розкриттю сутності економіко-психологічних явищ та формулюванню концептуальних положень.
Сучасні перспективи дослідження економічної психології
Keywords: business sector; corporate social responsibility; business strategy; environmental risks; responsible business; banking sector; business environment; investor; client; бізнес-сектор; корпоративна соціальна відповідальність; бізнесстратегія; екологічні ризики; відповідальний бізнес; банківський сектор; бізнес-середовище; інвестор; клієнт.